Power Consumption Analysis of UAVs with Varying Payloads for Next Generation Wireless Networks - Ahmed, Saif; Emon, Nimul Islam (MIST International Journal of Science and Technology, 2025)
Unmanned Aerial Vehicles (UAVs) are emerging as an important component for enhancing the coverage and capacity of next generation wireless networks. However, the use of UAVs is challenging because of crucial power management. The power management becomes more sophisticated for rotary-wing UAVs, the most commonly used ones, which require more energy as payload and flight actions increase. The current study investigates the energy consumption of UAVs with varied payloads during hovering and moving operations. The effects of payloads such as cameras, sensors, GPS modules, communication systems, and flight controllers on UAV power consumption are investigated in this study. It is very much necessary to comprehend these energy dynamics for optimal UAV design and maximizing operational effectiveness. Key findings show how payload configuration and flying conditions affect energy requirements. Two regression-based empirical mathematical models for hovering and moving conditions representing the relationship between the power consumption of UAV and its weight with payloads are proposed. This rigorous analysis of power consumption of UAV provides valuable insights into optimizing UAV design and operation in next-generation wireless networks. The findings of the work, including the proposed mathematical models, are expected to help researchers and engineers develop more energyefficient UAVs, resulting in extended flight periods and improved operational reliability. MIJST, V. 13,December 2025: 85-95 https://doi.org/10.47981/j.mijst.13(02)2025.511(85-95)